2014
DOI: 10.4236/aim.2014.48047
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation on the Effect of <i>Lactobacillus</i> and Epidermal Growth Factor on Tight Junction Proteins in Experimental Clostridium <i>difficile</i> Infection

Abstract: Clostridium difficile associated disease (CDAD) is the most common hospital acquired infection, due to exposure to various drugs. C. difficile toxins influence barrier function in intestinal epithelium. Biotherapeutic approaches, employing probiotic and epidermal growth factor (EGF) could help in barrier protein protection and aid in CDAD management. A preliminary investigation on the effect of Lactobacillus acidophilus and EGF on tight junction proteins in experimentally induced C. difficile infection was don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In the published literature, the role of EGF is mainly seen in a protection of the EB against stressing conditions rather than directly improving the EB (Banan et al, 2003;Basuroy, Seth, Elias, Naren, & Rao, 2006;Guntaka, Samak, Seth, LaRusso, & Rao, 2011;Koepke et al, 2015;Okuyama et al, 2007;Sheth, Seth, Thangavel, Basuroy, & Rao, 2004). It often prevented or decreased the detrimental effect of micro-organisms on the epithelial barrier (Buret, Mitchell, Muench, & Scott, 2002;Kaur, Vaishnavi, Ray, Singh, & Kochhar, 2014;Lamb-Rosteski et al, 2008). EGF does so by stimulation of several intracellular pathways involved in TJ modulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the published literature, the role of EGF is mainly seen in a protection of the EB against stressing conditions rather than directly improving the EB (Banan et al, 2003;Basuroy, Seth, Elias, Naren, & Rao, 2006;Guntaka, Samak, Seth, LaRusso, & Rao, 2011;Koepke et al, 2015;Okuyama et al, 2007;Sheth, Seth, Thangavel, Basuroy, & Rao, 2004). It often prevented or decreased the detrimental effect of micro-organisms on the epithelial barrier (Buret, Mitchell, Muench, & Scott, 2002;Kaur, Vaishnavi, Ray, Singh, & Kochhar, 2014;Lamb-Rosteski et al, 2008). EGF does so by stimulation of several intracellular pathways involved in TJ modulation.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal development is related to the intestinal barrier integrity directly, to keep intestinal health, and intracellular homeostasis is essential for the formation of the intestinal barrier. Pervious study has shown EGF controlling mucosal homeostasis through regulating the tight junction components [ 9 , 40 ], enhancing the mucins secretion [ 41 , 42 ], and decreasing pathogens colonization [ 8 , 27 30 ].…”
Section: Egf and Intestinal Developmentmentioning
confidence: 99%
“…In addition, EGF can reduce C. jejuni colonization in the jejunum of C. jejuni infected chicks and prevent C. jejuni -induced claudin-4 disruption [ 30 ]. What is more, EGF showed a protective effect on TJs in experimental Clostridium difficile (C. difficile) infected mice [ 9 ], suggesting a potential role of EGF in reducing C. difficile colonization.…”
Section: Egf and Intestinal Barriermentioning
confidence: 99%
See 2 more Smart Citations